Importance of sagittal kick symmetry for underwater dolphin kick performance - Atkison, R. R.; Dickey, J. P.; Dragunas, A.; Nolte, V. (Human Movement Science, 2013)
The purpose of this study was to determine how sagittal kick symmetry in the underwater dolphin kick (UDK) between the downkick and upkick phases is related to UDK performance. Fifteen adult male competitive swimmers ranging from provincial to international level were filmed performing three trials each of maximum effort UDK over 15 m using an underwater video camera. Video frames were manually digitized and each subjects` single fastest trial was evaluated for between-subject comparisons. Kinematic variables were calculated for each individual and Pearson product-moment correlations between the average horizontal centre of mass velocity (Vx) and all kinematic variables were calculated. Horizontal velocity during the downkick, horizontal velocity during the upkick, relative time spent in each phase, maximum chest flexion angle, maximum knee and ankle extension angles, the ratio of flexion/extension for chest, knee and ankle angles, and maximum vertical toe velocity during the upkick phase correlated significantly with Vx (p < 0.05). The ratio of downkick vertical toe velocity/upkick vertical toe velocity was significantly negatively correlated with Vx (p < 0.05). These results indicate the importance of kick symmetry for UDK performance, and indicate that performing the upkick phase well appears to be most important for UDK performance.